Effects of Tb(3+) dopants in the La1-x Sr x MnO3 bulk and nanoparticle ferromagnets - Kaman, Ondřej; Hejtmánek, Jiří; Jirák, Zdeněk; Knížek, Karel; Maryško, Miroslav; Novák, Pavel; Vratislav, Stanislav (Journal of physics. Condensed matter, 2016)
Three forms of La,Sr-manganites are synthesized and the role of Tb doping is investigated. First two systems are sol-gel nanoparticles and sintered ceramics of the composition La0.56Tb0.07Sr0.37MnO3, whereas the third system is formed by comparable nanoparticles La0.51Tb0.06Sr0.43MnO3 synthesized in molten salt. The samples show pseudocubic perovskite structure with only small tilts of MnO6 that point to Ibmm symmetry in the bulk and [Formula: see text] symmetry in nanoparticles. SQUID magnetometry and neutron diffraction reveal a complete FM order of Mn spins in bulk, a reduced order in nanoparticles, and non-zero moments at A sites. Detailed analysis suggests that the dodecahedral coordination of A sites adapts to small terbium size, and the resulting crystal field splitting of Tb(3+) yields a singlet ground state. The response to exchange and external fields is characterized as a giant Van Vleck paramagnetism in contrast to the Curie-type behaviour of Tb-based orthoaluminates and orthocobaltites with the quasi-doublet ground state.